МУЗЫКАЛЬНАЯ ОНТОЛОГИЯ Ф. НИЦШЕ И ПОНЯТИЕ «ВРЕМЯ» - ШАПЧЕНКО, Т. В. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
Статья посвящена музыкальной онтологической концепции Ф. Ницше и понятию«времени», через которое можно выразить суть его взглядов на онтологию музыки. Внастоящей работе дается определение и анализ двух ключевых понятийнатуралистической онтологии Ницше – «диониссийское и аполлоническое». Эти двекатегории истолковываются как оппозиция Бытия и Становления, где «аполлоническое»есть статическое бытие и постоянство, а «диониссийское» – динамическоестановление, развертывание и изменение. На основании музыкальной онтологии Ницше вданной статье отождествляется понятие становления с понятием времени, что вперспективе может позволить построить еще одну концепцию времени.Шапченко Т. В. МУЗИЧНА ОНТОЛОГІЯ Ф. НІЦШЕ ТА ПОНЯТТЯ «ЧАСУ»Стаття присвячена музичній онтологічній концепції Ф. Ніцше і поняттю «часу», черезяке можна висловити суть його поглядів на онтологію музики. В даній роботі даєтьсявизначення і аналіз двох ключових понять натуралістичної онтології Ніцше –«діонісійське і аполлонічне». Ці дві категорії тлумачаться як опозиція Буття іСтановлення, де «аполлонічне» є статичне буття і сталість, а «діонісійське» –динамічне становлення, розгортання і зміна. На підставі музичної онтології Ніцше вданій статті ототожнюється поняття становлення з поняттям часу, що вперспективі може дозволити побудувати ще одну концепцію часу поряд з вже існуючими.Ключові слова: онтологія, музика, час, становлення, «діонісйське і аполлонічне»,розгортання., сенс.Shapchenko T.V. MUSICAL ONTOLOGY OF F. NIETZSCHE AND THE NOTION OF«TIME» The art of music takes a special place in the life of every individual and in the history ofhuman civilization on the whole. Music as a form of art brings forth numerous philosophicaldisputes and speculations – what music is, what the ontological nature of various musicalgenres, styles and compositions is, philosophical value and epistemological meaning of musicalartifacts, search for the sense of music and the role of individual musical experience.F. Nietzsche, the German philosopher and representative of irrationalism, made asignificant contribution in the ontology of music. Nietzsche’s ontological concept and the notionof “time”, whereby the main points of his views on the ontology of music can be expressed, areconsidered in this article. A definition and analysis of the two key notions of Nietzsche’snaturalistic ontology – “Dionysian” and “Apollonian” are offered in this work. These twocategories are interpreted as the opposition of Being and Becoming, where “Apollonian” isstatic being and “Dionysian” is dynamic becoming, development and reformation. The symbolicimages of Apollo and Dionysus embody fundamental image spheres of the Antique culture.Nietzsche gives preference to “Dionysian” principle as to the embodiment of the ontologicalnotion of Becoming. He states that ‘“dionysism” is a more absolute “spirit of music” and it ismore relevant to the essence of music, which implies dynamics, evolution, reformation,movement, harmonic and rhythmic abundance. Following this interpretation of music asbecoming, it can be seen as a temporal category and a universal language, which is used todescribe all dynamical processes of objective and subjective reality.It stands to reason that this description is figurative and symbolic, but not conceptual andlogical. However, the fundamental issue in this work is that on the basis of Nietzsche’s musicalontology, the notion of becoming is identified with the notion of time, which in perspective canenable us construct another concept of time alongside with the existing already concepts(physical time, subjective psychological time, biological, social etc.) – the concept of musicaltime. In this hypothetical concept time, first of all, is a successive development of musical sensesand symbols in the form of a sound flow, which is a developing musical event, a process ofbecoming in the process of perception and comprehension.As in all other concepts, in this one time is continual; it doesn’t have any gaps or discreteparts. Musical time can be analyzed as an interlink between the concepts of natural time(physical, biological) and the concept of subjective psychological time, as temporalcomprehension of musical events is expressed in physical sound effects and can be realized onlyin the subjectivism of human mentality. A similarity between the “Dionysian” principle ofNietzsche’s musical ontology and images of modern electronic music can be noticed in themodern specialized literature,Key words: ontology, music, time, becoming, Dionysian and Apollonian, development,sense.